Molecular cloning and characterization of heat-responsive LcOPR1, a gene encoding oxophytodienoic acid reductase in lentil: Characterization of heat-responsive lentil gene - Abu-Romman, Saeid; Mbarki, Sonia; Al-Momany, Bayan; Skalicky, Milan; Brestic, Marian; Alalawy, Adel I.; Pandey, Saurabh; Alasmari , Abdulrahman; M. Alzuaibr, Fahad; Sakran, Mohamed; Ercisli, Sezai; El-Sharnouby, Mohamed; et al. (Cellular and Molecular Biology, 2024)
Improving crop plants using biotechnological implications is a promising and modern approach compared to traditional methods. High-temperature exposure to the reproductive stage induces flower abortion and declines grain filling performance, leading to smaller grain production and low yield in lentil and other legumes. Thus, cloning effective candidate genes and their implication in temperature stress tolerance in lentil (Lens culinaris Medik.) using biotechnological tools is highly demandable. The 12-oxophytodienoic acid reductases (OPRs) are flavin mononucleotide-dependent oxidoreductases with vital roles in plants. They are members of the old yellow enzyme (OYE) family. These enzymes are involved in the octadecanoid pathway, which contributes to jasmonic acid biosynthesis and is essential in plant stress responses. Lentil is one of the vital legume crops affected by the temperature fluctuations caused by global warming. Therefore, in this study, the LcOPR1 gene was successfully cloned and isolated from lentils using RT-PCR to evaluate its functional responses in lentil under heat stress. The bioinformatics analysis revealed that the full-length cDNA of LcOPR1 was 1303 bp, containing an 1134 bp open reading frames (ORFs), encoding 377 amino acids with a predicted molecular weight of 41.63 and a theoretical isoelectric point of 5.61. Bioinformatics analyses revealed that the deduced LcOPR1 possesses considerable homology with other plant 12-oxophytodienoic acid reductases (OPRs). Phylogenetic tree analysis showed that LcOPR1 has an evolutionary relationship with other OPRs in different plant species of subgroup I, containing enzymes that are not required for jasmonic acid biosynthesis. The expression analysis of LcOPR1 indicated that this gene is upregulated in response to the heat-stress condition and during recovery in lentil. This study finding might be helpful to plant breeders and biotechnologists in LcOPR1 engineering and/or plant breeding programs in revealing the biological functions of LcOPR1 in lentils and the possibility of enhancing heat stress tolerance by overexpressing LcOPR1 in lentil and other legume plants under high temperature.